IMPLEMENTATION OF HAZARD ANALYSIS CRITICAL CONTROL POINT (HACCP) ON SUGARCANE ICE TRADERS IN MEDAN CITY IN 2024 - Ashar, Yulia Kharina; Safira, Putri; Lauchan, Agil Maritho; Elvina, Elvina; Rahmadanty, Dwi Azura; Saragih, Eka Fitria; Sinambela, Nur Delina; Putri, Amelia; Purba, Sumiarti (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
HACCP is implemented as a systematic approach to identify, evaluate, and control potential hazards in sugarcane ice production to ensure food safety. The purpose of this research is to find out the implementation of the HACCP system carried out by sugarcane ice drink traders in Medan City in 2024. This study uses a qualitative analytical approach focused on sugarcane ice drinks sold in Medan City. The research subjects consisted of 33 sugarcane ice drink traders operating in the Medan City area. The results of the study on the implementation of HACCP on sugarcane ice traders in the city of Medan in 2024 found significant findings that the majority of sugarcane ice traders are in the productive age range of 35-49 years (48.5%), with a gender composition that is almost balanced between men (45.5%) and women (54.5%). The highest level of education is junior high school graduates (45.5%), with most traders operating for 6-10 hours per day (57.6%) and having 1-5 years of selling experience (60.6%). Traders' knowledge of hazards is still very low, only 6.06% know, and the majority are unaware of the dangers of E. coli bacteria (78.79%). However, the habit of washing hands before processing drinks is quite good (78.79%), and all traders understand the importance of clean containers before use (100%). Observations show that hygiene and sanitation are rated good by 60.6% of traders, but temperature control, supervision, and risk control still need to be improved. Documentation is also a major problem with 93.9% of traders rated as poor.